2023
DOI: 10.3390/life13030638
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Transperineal MRI/US Fusion Prostate Biopsy: 4-Year Experience

Abstract: This study aimed to evaluate the learning curve of transperineal magnetic resonance imaging (MRI)/ultrasound (US) fusion biopsy in a team composed of a single surgeon, a single radiologist, and a single pathologist. We prospectively enrolled 206 patients undergoing MRI/US fusion prostate biopsy and divided them into four cohorts by the year of biopsy. We analyzed temporal changes in clinically significant prostate cancer (csPC) detection rate, percentage of positive cores on biopsy, and Gleason upgrading rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…also have shown an impact of operators’ expertise on cancer detection rate, but possibly more pronounced for transrectal than for transperineal fusion biopsies with a steep phase of about 60 cases [ 18 ]. Hsieh et al reported that TPFBx under general anaesthesia learning curve shows significant improvement over a 4-year period [ 26 ]. Meng and coll.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also have shown an impact of operators’ expertise on cancer detection rate, but possibly more pronounced for transrectal than for transperineal fusion biopsies with a steep phase of about 60 cases [ 18 ]. Hsieh et al reported that TPFBx under general anaesthesia learning curve shows significant improvement over a 4-year period [ 26 ]. Meng and coll.…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, we have investigated the LCs through several independent statistical methods on prospectively acquired data: CPGs fractions and medians trends, logistic/linear regression and CUSUM analyses; this overcomes the limitation imposed by arbitrarily defined group segmentation of other similar reports and enhances the robustness of our findings [ 19 , 28 ]. Our work is not devoid of limitations: no central MRI review was performed and heterogeneity in imaging was not assessed; the number of operators, their previous experience and the disease prevalence were different amongst included centres; the length of the biopsy series considered for each operator is limited, and therefore our results might reflect mainly the early phase of the learning curve; a single fusion biopsy platform (Esaote) was employed; no analysis on biopsy needle trajectory, percentage of tumour on positive cores, ratio of upgrading at final pathology was performed [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no endorectal coil was used. The scanning protocol was performed as described previously (19,20), and images were interpreted by two radiologists. The T2WI was used for contouring the prostate and targeted lesions, and then a 3-D model of the prostate targeted lesions was built using a BioJet (D&K Technologies GmbH, Barum, Germany) or bkFusion (BK Medical, Herlev, Denmark) system.…”
Section: Subjectsmentioning
confidence: 99%
“…Prostate biopsies represent the cornerstone of prostate cancer (PCa) diagnoses, with over one million procedures having been performed in Europe and in the United States [ 1 , 2 ]. Prostate biopsies are usually performed under local anesthesia either transrectally or transperineally [ 3 , 4 ]. Although several studies have demonstrated the superiority of the trans-perineal route over the transrectal route in terms of the detection rate and complications, the transrectal route is still the most widely used one [ 5 ].…”
Section: Introductionmentioning
confidence: 99%